Multimedia Resources and Sporting Bias in MARCA.com and SPORT.es: An Analysis of Matches between Real Madrid C. F. and F. C. Barcelona (2010 - 11) (2015)
The increasing potency of identity politics across Europe often sees sport acting as a vehicle for the promotion and celebration of regional and sub-national identities. However, while the relationship between sport, the media and national identity has featured in numerous academic and political debates in recent years, the links between sports media and regional identity have received little attention. This seems a curious oversight, because the links between sport and region frequently become a celebration of the local and the distinctive, emblematic of community and continuity. This volume will explore that sense of the counter-hegemonic, where sport is celebrated by a media often keen to promote notions of difference, which might verge on rebellion in some contexts, conceived as resisting global homogeneity or national hegemony. At other times, they may merely reflect a commercial nose for the local audience’s tastes, but there is always the sense of preserving something important, a celebration of the diversity that makes us human. This book considers the centrality and cultural significance of particular sports, or clubs, to regional and sub-national identities across Europe and beyond, adopting a comparative approach to the mediatized nature of such portrayals.